TEACHING OF PATIENT SAFETY IN UNDERGRADUATE NURSING COURSES - Silva, Stephanye Vithória Martins da; Haddad, Maria do Carmo Fernandez Lourenço; Dadalt, Patrícia Aroni; Silva, Larissa Gutierrez de Carvalho (Cogitare Enfermagem, 2024)
Objective: To identify the insertion of the theme “Patient Safety”, as a separate discipline, in undergraduate Nursing courses in the State of Paraná – Brazil. Method: Exploratory, descriptive, documentary-type study, with a quantitative approach, developed through analysis of information described in the curriculum guidelines, collected in January 2023 and analyzed using the document analysis method. Results: Of the 54 undergraduate nursing courses offered in the State of Paraná, nine teach specific subjects on the topic “patient safety”, three in public institutions and six in private institutions. Conclusion: Curricular weaknesses were observed in the approach to this topic, with a noticeable need to introduce concepts about patient safety into the curricular guidelines, integrating theory into professional practice.